The Effectiveness Of The Use Of Learning Technology In The Management Of Islamic Education In The Digital Era - Selamet Setiawan; Mohammad Alfi Syahrirn; Mahi Sultan Salama; Salatou Touray (JURNAL PEDAGOGY, 2026)
The importance of learning technology in the context of Islamic education management in the digital era is the main study in this study. Through an in-depth analysis, this study examines the extent to which the use of learning technology has had a positive impact on the effectiveness of Islamic education management in the digital era. This research is a descriptive qualitative research with a literature review. The data collected came from scientific journals related to the use of learning technology. The data obtained was then analyzed by descriptive analysis method. The results of the study show that: (1) the integration of learning technology in the Islamic education curriculum highlights the importance of the use of technology as a tool to increase the effectiveness, efficiency, and relevance of Islamic education in the modern era. (2) Increased student participation and involvement in the application of learning technology shows that technology has great potential to improve student interaction, motivation, and learning outcomes. (3) the role of Islamic religious education teachers in technology-based learning is very important. Teachers not only play the role of teachers, but also as leaders, facilitators, mentors, and role models for students in the use of technology to deepen students' understanding of Islam. (4) the role of educational institutions in optimizing the management system of Islamic education development in the digital era illustrates the importance of adapting to changing times and the use of technology to improve the quality and relevance of Islamic education. Overall, the results of this analysis provide comprehensive insight into the extent of the effectiveness of the use of learning technology in the management of Islamic education in the digital era. The implications of these findings can help the formulation of policies and best practices to maximize the positive potential of learning technologies in the context of Islamic education.